2002
DOI: 10.1029/2001jd001568
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Atlantic Spring Experiment 1997 (EASE97) 2. Comparisons of model concentrations of OH, HO2, and RO2 with measurements

Abstract: [1] An observationally constrained box model has been used to investigate the chemistry of the marine boundary layer at the Mace Head Atmospheric Research Station, a remote site on the west coast of Ireland. The model aims to simulate concentrations of the hydroxyl (OH) and hydroperoxy (HO 2 ) radicals measured by an in situ fluorescence assay by gas expansion instrument, and the sum of peroxy radicals , respectively, between 1100 and 1500 hours: the level of agreement is better for all three sets of radicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 46 publications
5
98
1
Order By: Relevance
“…The peroxy radical chemical amplifier technique (Hastie et al, 1991;Cantrell et al, 1984) has been used in a large number of campaigns (e.g. Platt et al, 2002;Carslaw et al, 2002;Monks et al, 1996;Cantrell et al, 1996). In a recent field campaign (Platt et al, 2002), it was shown to compare well with direct RO x measurements made using Matrix Isolation/Electron Spin Resonance (MIESR) (Mihelcic et al, 1990).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations
“…The peroxy radical chemical amplifier technique (Hastie et al, 1991;Cantrell et al, 1984) has been used in a large number of campaigns (e.g. Platt et al, 2002;Carslaw et al, 2002;Monks et al, 1996;Cantrell et al, 1996). In a recent field campaign (Platt et al, 2002), it was shown to compare well with direct RO x measurements made using Matrix Isolation/Electron Spin Resonance (MIESR) (Mihelcic et al, 1990).…”
Section: Methodsmentioning
confidence: 79%
“…Model results have tended to overestimate the OH concentration (Carslaw et al, 2002(Carslaw et al, , 1999George et al, 1999), with the PROPHET campaign representing a significant exception. Constraining the HO 2 or RO x concentration using measured values tends to result in much better agreement between model results and measurements (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of halogens in HO x chemistry was demonstrated during the NAMBLEX campaign in Mace Head, Ireland , following several studies which attributed box model overestimates of HO 2 observations in marine environments to unmeasured halogen monoxides (Carslaw et al, 1999Kanaya et al, 2001Kanaya et al, , 2002Kanaya et al, , 2007. Simultaneous measurements of OH and HO 2 by laserinduced fluorescence (LIF) (Bloss et al, 2005a;Smith et al, 2006) and halogen species by a combination of DOAS (for BrO or IO, OIO and I 2 ) and broadband cavity ring-down spectroscopy (BBCRDS) (for OIO and I 2 ) (Bitter et al, 2005) during NAMBLEX enabled box model calculations to fully explore the impacts of halogens on the local composition.…”
Section: Introductionmentioning
confidence: 99%